Ніцшеанський дискурс у прозі Валер’яна Підмогильного - Протасова, Г. (Літературознавчі обрії. Праці молодих учених, 2010)
In the article the Nietzschean discourse of Valerjan Pidmohylny’s prose is analyzed. The author starts with the presumption that basic Nietzschean concepts – such as the opposition «Apollonian – Dionysian» in human culture, the antinomy of moral and aesthetical, the concept of superman give necessary structural shape to the writer’s texts, from his early short stories to the last unfinished work «Povist’ bez nazvy» («Story without a Title»), which gives birth to a Nietzschean hero with all essentially Nietzschean features. The analysis is made on the base of Nietzsche’s interpretation produced by the most influential philosophers of the 2nd half of the 20th century such as K. Jaspers, M. Heidegger, and J. Deleuze.